School management in transition : schooling on the edge - Shuttleworth, Dale E. (Dale Edwin), 1938- (Student outcomes and the reform of education., 2003)
This book draws on an OECD survey that sets out to identify innovation and good practice in school management in nine of the world's most industrialised countries. The book describes what is being done to improve educational management among these.